Effect of wheat spike infection timing on fusarium head blight development and mycotoxin accumulation. (31st July 2013) - Siou, D.; Gélisse, S.; Laval, V.; Repinçay, C.; Canalès, R.; Suffert, F.; Lannou, C.
<x xml:space="preserve">Abstract</x> Fusarium head blight in wheat spikes is associated with production of mycotoxins by the fungi. Although flowering is recognized as the most favourable host stage for infection, a better understanding of infection timing on disease development and toxin accumulation is needed. This study monitored the development of eight characterized isolates of F. graminearum, F. culmorum and F. poae in a greenhouse experiment. The fungi were inoculated on winter wheat spikes before or at anther extrusion, or at 8, 18 and 28 days later. Disease levels were estimated by the AUDPC and thousand‐kernel weight (TKW). The fungal biomass (estimated by qPCR) and toxin concentration (deoxynivalenol and nivalenol, estimated by UPLC‐UV‐MS/MS) were measured in each inoculated spike, providing a robust estimation of these variables and allowing correlations based on single‐individual measurements to be established. The toxin content correlated well with fungal biomass in kernels, independently of inoculation date. The AUDPC was correlated with fungal DNA, but not for early and late infection dates. The highest disease and toxin levels were for inoculations around anthesis, but early or late infections led to detectable levels of fungus and toxin for the most aggressive isolates. Fungal development appeared higher in kernels than in the chaff for inoculations at anthesis, but the opposite was found for later inoculations. These results show that anthesis is the most susceptible stage for FHB, but also clearly shows that early and late infections can produce significant disease development and toxin accumulation with symptoms difficult to estimate visually.